PEMBERHENTIAN DIREKSI DAN DEWAN PENGAWAS PERUSAHAAN UMUM DAERAH (PERUMDA) PENAJAM BENUO TAKA ENERGI: The Dismissal of the Directors and Supervisory Board of the Regional Public Company (Perumda) Penajam Benuo Taka Energi - Muhammad Reza Akbar Fachrezi; Arif Wicaksana (AMICUS CURIAE, 2025)
The Regional Public Company called Penajam Benuo Taka Energi (PBTE) is a Regional Owned Enterprise which was formed in the framework of North Penajam Paser Regency's participation in share ownership through a Participating Interest (PI) mechanism. However, along with the capital investment, the Main Director of Perumda PBTE violated Article 65 jo. Article 66 PP No. 54/2017, which resulted in the issuance of PPU Regent Decree No. 539/122/2022. With problem identification, namely how a Perumda carries out activities related to the management of Perumda or legal relations with other parties, if there is a vacancy in the board of directors at Perumda Penajam Benuo Taka Energi. The result and the conclusion as a result, since the issuance of the decree, there has been a vacancy in the board of directors at Perumda PBTE. By the provisions of Article 71 paragraph (1) PP 54/2017, "In the event of a vacancy in the positions of all members of the Board of Directors." Based on these provisions, North Penajam Paser Regent Decree No. 539/123/2022 was issued concerning the Appointment of the Supervisory Board as the Acting Task Force (Plt) of Perumda PBTE, specifically the Supervisory Board of Perumda PBTE.